ANALISIS KNOWLEDGE SHARING DALAM INOVASI BISNIS UNTUK MENINGKATKAN KINERJA USAHA MIKRO KABUPATEN CIANJUR MENGGUNAKAN PARTIAL LEAST SQUARE - Fauzi, Moch Restu; Putro, Bramantiyo Eko (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
The Cianjur Diskoperindagin recorded that 2,715 new MSMEs had emerged. However, Cianjur micro businesses experienced a significant decline in sales, making it difficult to design and implement marketing strategies. Therefore, micro businesses are required to produce quality, competitive products that have high competitiveness and to continue to innovate in terms of product development and sales. This research seeks to analyze the effectiveness of micro-enterprise knowledge sharing through business innovation. Research data was obtained by distributing questionnaires to 140 micro business actors in Cianjur. Data and conceptual models were tested using the PLS-SEM method with the help of SmartPLS4 software. The research results show that the tacit knowledge sharing variable is explained by the variables trust, organizational structure and employee attitudes with a variance value of (10%). Meanwhile, the explicit knowledge sharing variable can be explained by the variables trust, organizational culture, employee attitudes and motivation methods with a variance of (20%). The quality of innovation in this research can be explained by explicit and tacit knowledge sharing with a variance value (12%). This is different from the speed of innovation which can only be explained by tacit knowledge sharing with a variance of (11%). This research also shows that the operational and financial performance of micro businesses in Cianjur can only be explained by the speed of innovation variable.